ANALISIS BUKU AJAR BIOLOGI SMA KELAS X BERDASARKAN ASPEK LITERASI LINGKUNGAN - Aprilia, Nani; Irawati, Hani; Asri, Gita Amalia; Suharno, Suharno; Wulandari, Indah; Sula, Sula (BIOEDUKASI (Jurnal Pendidikan Biologi), 2023)
Environmental literacy is a person's conscious attitude in protecting the environment so that the balance is maintained. The impact of the environmental approach in learning can bring out students' curiosity about the environment around them, for example through textbooks. The phenomenon of textbooks, especially biology, needs to be reviewed to adapt to the current context, namely the issue of environmental damage. However, in reality biology textbooks do not provide a portion in instilling environmental literacy so that students' environmental literacy is low. The purpose of this study was to determine the percentage of aspects of environmental literacy in class X high school biology textbooks, to find out whether the class X high school biology textbooks support environmental literacy-based learning, to analyze the scope of environmental literacy in class X high school biology textbooks. Research This is a descriptive study, using a quantitative approach to analyze the Biology textbooks for class X SMA published by Erlangga and Yudhistira. The object of this study was the even semester material in class X high school biology textbooks and the subject of this research was the class X high school biology textbook published by Erlangga and Yudhistira. Selection of research subjects using purposive sampling. The data collection technique used was observation and the instrument used in this study was an observation sheet to analyze the content of aspects of environmental literacy in class X high school biology textbooks on even semester material. This instrument uses a guttman rating scale with intervals (yes/no). The data analysis technique performed in this study used a quantitative descriptive technique. Based on the results of the study, it was concluded that the level of environmental literacy textbooks for class X high school biology used in the city of Yogyakarta was in the low category. In the odd semester, textbook publisher A achieved a score of 24% and textbook publisher B achieved a score of 23.6%. Whereas in the even semester class X biology book the level of environmental literacy is also in the low category. The percentage in textbooks of publisher A was obtained by a percentage of 21% and for textbooks by publisher B was obtained by a percentage of 37%. The aspect that appears the most is the aspect of environmental knowledge, while the aspect that appears the least is the aspect of attitude.Kata kunci: Literasi Lingkungan, Buku Ajar, Biologi